Effects of climate, land cover and topography on soil erosion risk in a semiarid basin of the Andes - Ochoa Cueva, P. (2016)
Understanding soil erosion processes in the Ecuadorian Andes with a tropical wet-dry climate and a variable topography, is fundamental for research on agriculture sustainable, environmental management, as well as for a stable water supply for the local populations. This work proposes method to estimate soil erosion risk in the semiarid Catamayo basin with limited data. The results show that the rainfall distribution and the erosivity along with the rugged topography, followed by the land cover (C-factor), are the most important factors to estimate soil erosion risk. The soil erodibility is the most important factor in the dry season for agricultural areas and where the ground cover is sparse. Soil erosion risk is higher in the centre and southwest than in the northeast of Catamayo basin. In protected areas with evergreen vegetation, the soil erosion risk is very low, even with steep slopes and high annual rainfall amounts. The methodology developed allows understanding of the soil erosion processes and the factors that lead to the spatio-temporal variability of soil erosion risk, and as a consequence improves the potential to achieve sustainability of this ecosystem through proposed conservation measures.